Systemic lupus erythematosus in a male patient in lower Assam (Indian Journal of Case Reports, 2021)
Systemic lupus erythematosus (SLE) is one of the numerous diseases called “the great imitators” because it frequently resembles or is misdiagnosed as other illnesses. SLE is a chronic autoimmune inflammatory disorder that affects multiple systems and has a wide range of symptoms. The female to male ratio varies between 7 and 15 to 1. A number of observations point to an estrogen impact as the cause of this variance. Because sex hormonal impacts are likely to be modest in youngsters, the female to male ratio is 3:1. Renal involvement and seizures are more common in male SLE patients than photophobia and cutaneous symptoms. Males likewise appear to have a more devastating consequence. As a result, we feel that male lupus patients are uncommon, the illness’s symptoms are life-threatening, and that early discovery of the disease will result in a better outcome for these patients. Here, we report the case of SLE with an unusual presentation in a 44-year-old man from lower Assam to emphasize the importance of a high index of suspicion in such patients.